Stem Cell−Laden Coaxially Electrospun Fibrous Scaffold for Regenerative Engineering Applications. Issue 1 (21st January 2021) - Nagiah, Naveen; Franchi, Federico; Peterson, Karen; Rodriguez‐Porcel, Martin
Abstract: Stem cell−based therapies for various ailments have attracted significant attention for over a decade. However, low retention of transplanted cells at the damaged site has hindered their potential for use in therapy. Tissue engineered grafts with fibrillar structures mimicking the extracellular matrix (ECM) can be potentially used to increase the retention and engraftment of stem cells at the damaged site. Moreover, these grafts may also provide mechanical stability at the damaged site to enhance function and regeneration. Among all the methods to produce fibrillar structures developed in recent years, electrospinning is a simple and versatile method to produce fibrous structures ranging from a few nanometers to micrometers. Coaxial electrospinning enables production of a mechanically stable core with a cell‐binding sheath for enhanced cell adhesion and proliferation. Furthermore, this process provides an alternative to functionalized engineered scaffolds with specific compositions. The present article describes the protocol for developing a polycaprolactone (PCL) core and gelatin/gelatin methacrylate (GelMA) sheath laden with stem cells for various regenerative engineering applications. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Uniaxial PCL electrospinning Basic Protocol 2 : Coaxial electrospinning Support Protocol 1 : Scaffold characterization for Basic Protocols 1 and 2 Basic Protocol 3 : Cell seeding on uniaxial and coaxial electrospun scaffolds and MTS assay Support Protocol 2 : Preparation of scaffold with cells for scanning electron microscopy